Ambient-Dried Silica Xerogels with Enhanced Strength and Thermal Insulation via Calcium Ion-Glycerol Synergistic Crosslinking - Xiaoyu Xie; Zilin Zhu; Yu Meng; Lijia Wang; Fuquan Zhao; Lingqing Chen; Lijie Jiang; Ming Yan; Xiaofan Zhou (Gels)
Despite their high porosity and wide applicability, silica xerogels face mechanical strength limitations for high-performance applications. This study presents an ambient-pressure sol-gel strategy utilizing calcium-glycerol synergy to produce robust xerogels with enhanced properties. Physicochemical analyses reveal that controlled Ca2+ incorporation (optimal at 6 wt.%) accelerates gelation kinetics while establishing a hybrid network through ionic complexation and hydrogen bonding. The resulting xerogels achieve exceptional compressive strength (30.8 MPa) while maintaining uniform mesoporosity (50–90 nm pore size). Remarkably, the as-prepared silica xerogels demonstrate outstanding thermal insulation, maintaining a 220 °C temperature differential in 300 °C environments. These results prove that the ambient-pressure sol-gel strategy utilizing calcium-glycerol synergy can enhance the mechanical performance and thermal insulation performance of silica xerogels with the dual actions of Ca2+-induced network reinforcement via silanol coordination and glycerol-mediated stress relief during ambient drying. Overall, this work can offer a scalable, energy-efficient approach to produce high-performance silica xerogels with huge potential in building envelopes and aerospace systems.